Advances in Multimedia Modeling - Satoh, Shin'ichi (Springer, 2017)
Welcome to the 14th International Multimedia Modeling Conference (MMM 2008), held January 9–11, 2008 at Kyoto University, Kyoto, Japan. MMM is a leading international conference for researchers and industry practitioners to share their new ideas, original research results and practical development experiences from all multimedia related areas. It was a great honor to have MMM2008, one of the most long-standing m- timedia conferences, at one of the most beautiful and historically important Japanese cities. Kyoto was an ancient capital of Japan, and was and still is at the heart of Japanese culture and history.